Pengawasan Dewan Pengawas Syariah (DPS): Implementasi dan Efektivitas - Dawami, Ajrina; Santiasih, Putri (Program Studi Ekonomi Syariah IAIN Parepare, 2025)
Supervision by the Sharia Supervisory Board (DPS) in the Islamic finance industry is crucial to ensure that the implementation and consistency applied in Islamic banks comply with Sharia principles. This importance is underscored by the recent regulation issued by the Financial Services Authority (OJK) aimed at enhancing the supervision role of DPS in Islamic banks. The purpose of this research is to examine and analyze how the supervision conducted by DPS is implemented at Bank DKI KCP Syariah Ciputat. This study employs a qualitative method with case study analysis of previous research and interviews. The results indicate that the role of DPS is vital in the sustainability of bank activities, such as during the issuance of new products and when addressing community issues related to banking. DPS plays a crucial role in supervising various aspects, including products and activities, through fatwas to ensure they do not conflict with prevailing Sharia standards. Furthermore, the role of DPS is essential in Islamic banks for providing advice and guidance. Therefore, it can be concluded that DPS supervision plays a significant role, as it governs a vital aspect, namely controlling the Sharia compliance of a bank's products and activities.